2008
DOI: 10.1016/j.jallcom.2007.04.053
|View full text |Cite
|
Sign up to set email alerts
|

Copper(II) 15-metallacrown-5 lanthanide(III) complexes derived from l-serine and l-threonine hydroxamic acids

Abstract: Formation of pentanuclear copper(II) complexes with serine hydroxamic acid (Serha) and threonine hydroxamic acid (Thrha) was studied in solution by electrospray ionization mass spectrometry (ESI-MS), absorption spectrophotometry and proton NMR spectroscopy. The presence of lanthanide(III) ions is essential for the self-assembly of the 15-metallacrown-5 compounds. The positive mode ESI-MS spectra of the solutions containing Serha or Thrha, copper(II), and lanthanide(III) ions (Ln = La, Nd, Gd,) in the ratio 5:5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
1
3
0
1
Order By: Relevance
“…The ternary systems Eu 3+ or Gd 3+ /Cu 2+ /α-Alaha were initially studied by in-cell potentiometric titration, but a marked drift in the emf values was observed; thus, batch titrations were performed (see the Experimental Section). This inertness in the Ln 3+ 15-MC-5 formation in water was also recently put into evidence by Pacco and co-workers for ( S )-serine- and ( S )-threoninehydroxamic acids: their spectrophotometric study showed that the formation equilibrium was reached only 30 min after reactant mixing, although we have measured a drift in the emf readings within 12 h . In the present investigation, the titrations were limited to pH 6.5 because at higher pH the formation of an insoluble purple gelatinous material was observed.…”
Section: Resultssupporting
confidence: 80%
“…The ternary systems Eu 3+ or Gd 3+ /Cu 2+ /α-Alaha were initially studied by in-cell potentiometric titration, but a marked drift in the emf values was observed; thus, batch titrations were performed (see the Experimental Section). This inertness in the Ln 3+ 15-MC-5 formation in water was also recently put into evidence by Pacco and co-workers for ( S )-serine- and ( S )-threoninehydroxamic acids: their spectrophotometric study showed that the formation equilibrium was reached only 30 min after reactant mixing, although we have measured a drift in the emf readings within 12 h . In the present investigation, the titrations were limited to pH 6.5 because at higher pH the formation of an insoluble purple gelatinous material was observed.…”
Section: Resultssupporting
confidence: 80%
“…Nowadays, the popularity of water‐soluble polynuclear metallamacrocyclic Cu(II)‐Ln(III) complexes is largely due to their rich coordination chemistry, diverse properties and ease of synthesis . The remarkable feature of Cu(II)‐Ln(III) 15‐MC‐5 complexes is the deep color . It should be pointed out that the observed ligand‐field bands in visible region near 550 nm have provided the potential ability to obtain useful diagnostic information concerning the structures of transition metal ion‐peptide complexes .…”
Section: Introductionmentioning
confidence: 99%
“…The structural information gleaned from the pseudo-contact shifts can confirm or refute if the solid-state structure is retained in solution or if a series of molecules made with the same ligand set but different lanthanide ions are isostructural in solution. Almost all studies that have investigated a series of lanthanide complexes rely on complexes that contain one Ln III ion with a diamagnetic, organic ligand. Thus, little is known regarding the 1 H NMR behavior, and, in particular, the pseudo-contact shift properties of Ln III ions in the presence of paramagnetic 3 d transition metals. Metallacrowns (MC) are a class of molecules that offer a window into such investigations, which may result in unpredicted properties.…”
Section: Introductionmentioning
confidence: 99%